RELAY-BASED CO-OPERATIVE COMMUNICATION FOR WIRELESS NETWORKS – A SURVEY - Shachi P. (International Journal of Research Science and Management, 2016)
Fading is one of the serious issues of concern in a wireless communication [1]. The concept of spatial diversity led to the evolution of MIMO (Multiple-In Multiple-Out) systems which gave helped to mitigate the effects of fading but with the cost of increased hardware requirement. Co-operative communication which creates a virtual MIMO is a promising solution to overcome the effect of fading. It is one of the evolving techniques which offers reduced interference and error probability while providing increasedthroughput and power efficiency. This paper gives an overview of the co-operative communication, with more importance given to therelay-based co-operation. With a basic relay-network model, we have discussed on modes of operation of relay and various protocols for data-forwarding.